Fuzzy model tahani as a decision support system for selection computer tablet - Hafni Sahir, Syafrida; Rosmawati, R; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Tablet computer stores as tablet sales continue to keep pace with technology to meet the needs of consumers of tablet computer buyers, where consumers generally always have considerations or factors before taking a decision on a pur-chase, for example price, brand, screen size , memory, hard drive, or features present on the tablet computer and other factors. To be able to assist it, it needs to be supported into a computerized decision support system. Decision support sys-tems in addition to providing information can also help provide various alternatives that can be selected in the decision-making process. Fuzzy logic is a good way to map an input space into the output space. The research is expected to de-termine which type of tablet computer to choose based on the criteria desired by the user so that the user can easily deter-mine the option to buy a tablet computer based on features, facilities, and price, so that the brand of tablet computer can be purchased by the user.Â